Shifts in Klaipėda City Urbanonyms in 1903–1939 - Šiaulytė, Aistė (Acta humanitarica academiae Saulensis, 2026)
Klaipėda – Lithuania’s largest coastal city – belonged to different countries during the 20th century; therefore, its linguistic landscape is characterized by intense change linked to shifts in the political system. Although the official urbanonyms of this city most clearly reflect the peculiarities of the linguistic and cultural landscape, there has been no detailed analysis of the semantic motivation and strategies used to change the language of urbanonyms in the 20th century. There has been no systematic analysis of what strategy (direct translation, indirect translation, name change) was used when changing the language of urbanonyms. This article aims to analyse the semantic motivation and linguistic changes of Klaipėda’s official urbanonyms between 1903 and 1939. The chronological framework of the study covers periods of historical and sociocultural significance for the city of Klaipėda: 1903–1923 (during the German Empire’s rule until the Lithuanian takeover of the Klaipėda region), 1923–1939 (from the Lithuanian takeover of the Klaipėda region until the annexation of Klaipėda to Nazi Germany). The article presents an overview of Klaipėda socio-cultural landscape in the 20th century, including the relationship and change in the prestige of the Lithuanian and German languages, as well as the peculiarities of urbanonyms’ semantic motivation models and strategies of linguistic official urbanonyms change. After examining 246 official Klaipėda city urbanonyms, it was found that between 1923 and 1939, official urbanonyms were changed in two ways. The majority of urbanonyms (75,76%) were translated using a literal translation strategy, while 7,58% of official urbanonyms were not translated but changed. The change of urbanonyms most strongly affected the composition of the semantic groups of urbanonyms related to personal names and professions.